2018
DOI: 10.1002/uog.18930
|View full text |Cite
|
Sign up to set email alerts
|

Risk of spontaneous preterm birth in singleton pregnancies conceived after IVF/ICSI treatment: meta‐analysis of cohort studies

Abstract: Objective Preterm birth (PTB) is more common in pregnancies conceived by in-vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
109
3
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 45 publications
10
109
3
9
Order By: Relevance
“…The population‐based nature of the dataset that we used gave us the opportunity to examine baseline characteristics between infants with PVD born with and without the use of ART/NIFT. Similar to other epidemiological studies investigating ART, we found that preterm birth is much more common in infants exposed to ART/NIFT than with infants without exposure to maternal IT. While preterm birth is a common occurrence in multiple gestations associated with ART/NIFT, it is also two‐fold more frequent in singleton gestation generated by ART .…”
Section: Discussionsupporting
confidence: 90%
“…The population‐based nature of the dataset that we used gave us the opportunity to examine baseline characteristics between infants with PVD born with and without the use of ART/NIFT. Similar to other epidemiological studies investigating ART, we found that preterm birth is much more common in infants exposed to ART/NIFT than with infants without exposure to maternal IT. While preterm birth is a common occurrence in multiple gestations associated with ART/NIFT, it is also two‐fold more frequent in singleton gestation generated by ART .…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, several studies in the literature have shown that IVF/ICSI pregnancies themselves carry risks for obstetric complications and adverse perinatal outcomes compared with spontaneous pregnancies, even in singleton gestations . The risk of spontaneous preterm birth in singleton pregnancies resulting from IVF/ICSI is significantly greater than that in spontaneously conceived singletons according to a recently performed meta‐analysis of the cohort studies . In our study, monochorionic pregnancies and spontaneously conceived pregnancies were excluded and only ICSI singleton births were included in both the study and control groups, thus resulting in a homogeneous population.…”
Section: Discussionmentioning
confidence: 93%
“…3,4,8,9 The risk of spontaneous preterm birth in singleton pregnancies resulting from IVF/ICSI is significantly greater than that in spontaneously conceived singletons according to a recently performed meta-analysis of the cohort studies. 10 In our study, monochorionic pregnancies and spontaneously conceived pregnancies were excluded and only ICSI singleton births were included in both the study and control groups, thus resulting in a homogeneous population. Our study is also unique in that both infertility treatment and pregnancy followup of the study and control groups were in a single center, Bas¸kent University Ankara Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies have evaluated the potential benefit of pre-conception or early administration of low-dose aspirin in women with a history of recurrent pregnancy loss, (37)(38)(39)(40) women who have undergone in vitro fertilization (IVF) (28,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) or women with thrombophilia or antiphospholipid syndrome. (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) It is recognized that these women are at an increased risk of placenta-associated complications of pregnancy, including hypertensive disorder of pregnancy, (66)(67)(68)(69) preterm delivery, (70,71) and fetal growth restriction. (70,72) The objective of this study was to perform a systematic review and meta-analysis to estimate the effect of low-dose aspirin initiated at <11 weeks' gestation on the risk of preeclampsia, gestational hypertension, or any hypertensive disorder of pregnancy.…”
Section: Introductionmentioning
confidence: 99%